Comparison of the effects on cardiovascular events between use of metformin and dipeptidyl peptidase-4 inhibitors as the first-line hypoglycaemic agents in Japanese patients with type 2 diabetes mellitus: a claims database analysis - Rimei Nishimura; Tomomi Takeshima; Kosuke Iwasaki; Sumiko Aoi (BMJ Open)
Objectives To compare the risk of cardiovascular events from the initiation of therapy between metformin and dipeptidyl peptidase-4 inhibitors (DPP-4i) as first-line therapy.Design Retrospective cohort study using two claims databases.Setting The MDV database (provided by Medical Data Vision) comprised data from acute care hospitals, and the JMDC database (provided by JMDC) comprised data from individuals covered by health insurance societies.Participants Those who were diagnosed with type 2 diabetes at ≥18 years, prescribed metformin or DPP-4i as the first-line hypoglycaemic agent, had medical records of ≥6 months before the index prescription and had available glycated haemoglobin (HbA1c) data for the period, including the index date and 30 days before it (defined as the baseline) were included. Those diagnosed with type 1 diabetes and/or a history of myocardial infarction (MI) or cerebrovascular diseases were excluded.Primary and secondary outcome measures The outcomes were cumulative risks from Kaplan-Meier curves or HRs of patients prescribed metformin compared with DPP-4i. The primary endpoint was the diagnosis of MI or stroke associated with hospitalisation. Patient demographics, prescribed drugs and laboratory test values of HbA1c and estimated glomerular filtration rate at baseline were adjusted. The study period starting from the index included treatment after initial monotherapy.Results Overall, 2089 and 6686 patients in the MDV database and 1506 and 3635 in the JMDC database were prescribed metformin and DPP-4i, respectively. The HR of the primary endpoint was 0.879 with no statistical significance (95% CI 0.534 to 1.448, p=0.613) in the MDV database, while it was significantly lower, 0.398 (95% CI 0.213 to 0.742, 0.004) in the JMDC database.Conclusions Patients who received metformin as first-line therapy may have reduced cardiovascular events than those receiving DPP-4i. This study conforms to previous Japanese database studies, despite the consideration of its limitation being an observational design.